Optimized detection of particulates from liquid samples in the aerosol phase: Focus on black carbon. Issue 5 (4th May 2017) - Katich, Joseph M.; Perring, A. E.; Schwarz, J. P.
ABSTRACT: Operational parameters for a single particle soot photometer (SP2) and a CETAC Marin-5 nebulizer were optimized for detection of particulates aerosolized from liquid samples. The sensitivity of nebulization efficiency on nebulizer input gas pressure, liquid sample flow rate, and alcohol doping of the sample were explored. The nebulization efficiency of the Marin-5 was found to be roughly independent of applied gas pressure once above a minimum pressure. The nebulization efficiency changed by ∼50% for an order of magnitude change in liquid sample flow. Doping the sample with isopropyl alcohol at a 1:1 ratio results in a ∼50% relative increase in nebulization efficiency over a broad range of liquid flows. These results should apply to all particulate materials in the size range studied. SP2 operational parameters including sheath and sample flow were explored to optimize detection of refractory black carbon (rBC) specifically via coupling to the nebulizer. The SP2 tested samples up to 5 cc s−1 with 100% detection of rBC in its size range of detection, with increased sample jet spread and corresponding lack of detected rBC in the air at higher flows, leading to a total undetected rBC mass fraction of ∼15% at 16 cc s−1. Varying sheath flow does not improve this result, which is significant because under reasonable Marin-5 operating conditions, the SP2 only samples a fraction of the total air flow out of the nebulizer. Recommended operational parameters for cases of sample with low rBC loadings are presented: first, when very little liquid sample is available; second, when considerable sample is available. © 2017 American Association for Aerosol Research